2012
DOI: 10.1128/aem.02305-12
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Response of the Wine Yeast Saccharomyces cerevisiae EC1118 Grown under Carbon-Sufficient, Nitrogen-Limited Enological Conditions

Abstract: Discrete additions of oxygen play a critical role in alcoholic fermentation. However, few studies have quantitated the fate of dissolved oxygen and its impact on wine yeast cell physiology under enological conditions. We simulated the range of dissolved oxygen concentrations that occur after a pump-over during the winemaking process by sparging nitrogen-limited continuous cultures with oxygen-nitrogen gaseous mixtures. When the dissolved oxygen concentration increased from 1.2 to 2.7 M, yeast cells changed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 65 publications
4
51
1
Order By: Relevance
“…These data confirm respiratory metabolism as one major determinant of ethanol yields under these fermentation conditions. The RQ values obtained for S. cerevisiae are in agreement with our previous results (Quir os et al, 2014), as well as other authors, depending on the strain and growth conditions, RQ values ranging from 2.8 to ∞ have been described for S. cerevisiae under aerated glucose rich conditions (Aceituno et al, 2012;de Deken, 1966;Franzen, 2003). It is worth noting that oxygen consumed after 72 h in these cultures ranged from 1.9 g/L to 19.4 g/L (Supplementary file 2), far apart from the microgram or milligram range used in other enological applications.…”
Section: Resultssupporting
confidence: 91%
“…These data confirm respiratory metabolism as one major determinant of ethanol yields under these fermentation conditions. The RQ values obtained for S. cerevisiae are in agreement with our previous results (Quir os et al, 2014), as well as other authors, depending on the strain and growth conditions, RQ values ranging from 2.8 to ∞ have been described for S. cerevisiae under aerated glucose rich conditions (Aceituno et al, 2012;de Deken, 1966;Franzen, 2003). It is worth noting that oxygen consumed after 72 h in these cultures ranged from 1.9 g/L to 19.4 g/L (Supplementary file 2), far apart from the microgram or milligram range used in other enological applications.…”
Section: Resultssupporting
confidence: 91%
“…These findings are supported by the observed trends in proline utilisation, namely that QA23 utilised 300 mg/L of proline, regardless of oxygen availability, whereas, Q7, which achieved higher culture densities, assimilated significantly more proline: approximately 370 mg/L (self-anaerobic) or 730 mg/L (aerobic) (Figure 3). The latter results suggest that dissolved oxygen improved fermentation rates, as well as proline utilisation, which is consistent with previous studies [21,22,43]. At this stage, it is not possible to state whether the increase in growth in the presence of oxygen, is due to enhanced sterol and unsaturated fatty acid biosynthesis, and thereby improved cell condition [22], and/or enhanced proline catabolism by proline oxidase [21].…”
Section: Fermentation Performance Of Qa23 and Ems Isolate Q7 In Cdgjmsupporting
confidence: 80%
“…This observation is in line with expectations, since it has been reported that organic acid levels in wine will generally be significantly augmented under aerobic conditions compared to anaerobic conditions (Wiebel et al, 2008). An increase in succinic acid concentrations has previously been linked to the shift in central carbon metabolism of yeast from fermentative to respiratory (Larsson et al, 1993;Coulter et al, 2004;Aceituno et al, 2012). Under aerobic conditions, VIN13 remained the highest producer of succinic acid under both the white and red wine conditions (Fig.…”
Section: Figurementioning
confidence: 76%